Correlation Analysis between Manhour and Manpower in The Aircraft Structure Repair Division at Batam Aero Technic Hangar - Auwalia, Farda; Hayati, Nahrul (LPPM-ITEBA, 2025)
This study aims to analyze the correlation between manhours (working time) and manpower (labor) in the Aircraft Structure Repair Division at Batam Aero Technic Hangar, specifically for aircraft maintenance work on PK-LJQ 2024 with lightning strike damage. Using a quantitative approach with correlational analysis, secondary data in the form of historical operational records from 2024 were analyzed to measure the interdependence between these two variables. Pearson correlation test results showed a very strong positive relationship (r = 0,980; p < 0,05), with a coefficient of determination (r²) of 96,04%, indicating that 96.04% of manhour variation can be explained by manpower variation. Descriptive analysis revealed a proportional resource allocation pattern, where 180-minute jobs required 1 technician, 360–480-minute jobs required 2 technicians, and 720-minute jobs required 3 technicians. These findings prove that repair time efficiency is highly influenced by optimal labor allocation. This research provides practical implications for the aviation Maintenance, Repair, and Overhaul (MRO) industry in enhancing productivity by adjusting personnel numbers based on job complexity. The results can also serve as a basis for managerial decision-making in more efficient resource planning.